THE EAST AND WEST TRUST DEFICIT IN MOHSIN HAMID’S THE RELUCTANT FUNDAMENTALIST - Imtiaz, Uzma (European Scientific Journal, ESJ, 2015)
After fourteen years of the September 11 attacks, the international political landscape is still occupied with suspicion, confrontation and distrust. This study intends to explore the trust deficit between east and west as depicted by Mohsin Hamid in his novel The Reluctant Fundamentalist by Mohsin Hamid, and examine how far and how successfully he has portrayed the impact of 9/11 events on the Americans and the Muslims. By comparing the silent American (West) with Changez (East), Hamid has brilliantly discussed the relations between East and West. By revealing the conflicting viewpoints of the Americans and that of the Muslims, Hamid describes how East and West are similar or different in terms of the ideological meanings and sociopolitical situation. In order to make the comparison, I intend to apply the theoretical apparatus of Jean Baudrillard and investigate the extent to which Mohsin Hamid has portrayed the conflict between East and West in his novel, The Reluctant Fundamentalist. Since the research method is qualitative, the most appropriate method is the Critical Discourse Analysis model by Fairclough. In addition to East and West rift, the author also throws light on the political milieu after September 11attacks, including Pakistan-India issue and Afghanistan war as illustrated in the novel. This study, conducted as literary research, concludes that how successfully Hamid attempts to bridge the gap between east and west when he portrays them walking together in the same direction without any violation. However in the current political milieu the clash is between East and East when ISIS and the Taliban from East are attacking the eastern countries on a larger scale.